RESULTS OF OZONESONDE OBSERVATIONS AT SYOWA STATION IN 1990 - シバタ, セイジ; モリモト, マサオ; SHIBATA, Seiji; MORIMOTO, Masao (National Institute of Polar Research, 1992)
P(論文) Ozonesonde observations were carried out at Syowa Station in 1990 by meteorological members of the 31st Japanese Antarctic Research Expedition (JARE). The ozone continued to decrease rapidly from August to October. The ozone was destroyed almost completely between 80 and 100mb during the first ten days of October. The monthly mean of total ozone amount was the lowest ever observed at Syowa Station in August and September. The severe ozone depletion with ozone hole in 1990 was close to those in 1987 and 1989. We note that polar stratospheric clouds (PSCs) were observed at Syowa Station in winter. We estimated the height of PSCs from the angle between bright PSC edges and the sun. The heights were between 15 and 20km. When PSCs appeared, the extreme cold region under -83℃, enough for occurrence of type 2 PSCs, was observed with stratospheric soundings. departmental bulletin paper